EFEITO DOS PRECURSORES E TEMPERATURA DE TERMO-HIDRÓLISE NA FORMAÇÃO ÓXI-HIDRÓXIDOS DE FERRO - Müller, Marcelo (2015)
In this study, we investigated the influence of the precursor (ferric chloride hexahydrate and ferric nitrate nonahydrate) and temperature (50, 60, 70, 90 and 110 °C) synthesis of oxy-hydroxides of iron. The oxy-hydroxides formed coloration in various shades and were characterized with respect to structure, composition, spectroscopic behavior, etc., in order to investigate the properties which determine the variation of shades. Data from X-ray diffraction, Raman spectroscopy and chemical analysis by energy dispersive spectroscopy allowed to identify the synthesized phases, namely: Akaganeita (β-FeO (OH), yellow tones), Goethite (α-FeO (OH), yellow) and hematite (α-Fe2O3, red). Images of scanning electron microscopy (SEM) and histograms of dynamic light scattering (DLS) showed particles with nanometric sizes (between 150 and 300 nm), due to the synthesis temperature, the nanometer scale determines the color of the particle. Curves simultaneous thermal analysis (TG/DTG/DTA) for the particles obtained from the precursor ferric chloride present mass losses due to the disruption of structures at different temperatures (between 620 °C 530), suggesting different structural arrangements. Electronic spectra (UV-Vis) have profiles relating to variations of shades of colors, associated with the absorption variation (λ máximo) band due to charge transfer between Fe3+ ions and OH-/O2-. The particles of iron oxy-hydroxides have good dispersion in aqueous medium and have been used in commercial white pigment ink with higher degree of white coating.